On the valuation of real property for taxation - O'Brien, Murrough (Statistical and Social Inquiry Society of Ireland, 1879)
Thus in Ireland there are two different principles embodied in the Valuation Acts?one for the valuation of land, the other for the valuation of buildings; and the latter is the principle upon which the valuation of all property for taxation is made in England. In Ireland the great bulk of rateable property is in the form of land.
Read before the Society, 4 June 1878
Keywords: Property tax; Land tax; Property valuation; 314.15